DEVELOPMENT OF MATHEMATICAL LEARNING DEVICES USING PROBLEM SOLVING STRATEGY IN STAD-TYPE COOPERATIVE LEARNING MODEL ON PYTHAGORAS THEOREM MATERIAL - Romi Pirdaus (Jurnal Prinsip Pendidikan Matematika, 2022)
This research produces a product in the form of a mathematics learning device using the STAD type cooperative learning model on the Pythagorean Theorem material using problem solving strategies. The development model used is a 4-D model, namely Define, Design, Develop, and disseminate. The research instrument used is instrument validity and practicality. The validity instrument is in the form of a validation sheet to assess the validity of the learning tools, namely the syllabus, lesson plans, and LAS. The practicum instrument is a student response questionnaire to assess the usefulness and ease of use of LAS. The Learning Toolkit developed will be validated by three validators and revised according to the validator's suggestions. Subsequently, a small group trial was conducted with six students. The average value of syllabus validation is 3.76, lesson plans are 3.82, and LAS is 3.63, so the learning tools are categorized as very valid. The average result of the practicality of LAS is 85.95% in the very practical category. Based on the results of data analysis, it was concluded that this study produced a product in the form of mathematics learning tools using problem solving strategies with the STAD Type Cooperative learning model on the valid Pythagorean Theorem for Syllabus, RPP, and LAS. and practical for LAS.